Analisis Tataniaga Cabai Merah Dan Tomat Di Pasar Penampungan Kota Medan - Osman Manalu; Tumpal Halomoan Saritua Siregar; Abdul Rahman (JURNAL AGRICA, 2018)
This study aims to determine the types of marketing channels, marketing function in each channel marketing, marketing costs, share margins and prices spread on each channel as well the level of marketing efficiency in the red pepper and tomato Shelter Market Medan. This study uses field observation  and interview questionnaire, a population, of 75 respondents comprising 17 merchant traders village, town collectors 26 and 32 retailers in the market Shelter Medan. The model used data analysis is descriptive and quantitative analysis. The results showed that there were there (four) marketing channels in the red pepper and tomato Shelter Market Medan, Channels Marketing I : Farmers – Trade Village – City Traders – Trade Retailers – Konsumen, Channel Marketing II : Farmers – Trade Retailers – Consumers, Channels Marketing III : Farmers – Consumer. Each institution plays the marketing of at least 4 function, of which there are 4 2 channels apparently have a good level of efficiency than most other 2 channels for the smallest value of marketing efficiency. Keywords : Vegetable Soup, Chili, Tomato, Marketing, Channel Marketing, Efficiency